Fair value accounting in the absence of prudence in accounting standards: an illustration with exotic derivatives. Issue 2 (3rd April 2017) - Marabel-Romo, Jacinto; Guiral, Andrés; Crespo-Espert, José Luis; Gonzalo, José A.; Moon, Doocheol
ABSTRACT: The aim of this paper is to contribute to the current discussion about fair value accounting (FVA). We discuss the problem surrounding FVA by relying on the role played by prudence, its meaning, and how the treatment of prudence has changed in the accounting framework of standard setters due to its 'apparent' inconsistency with neutrality. To highlight the relevance of this issue, we provide (1) a brief analysis of the high impact that Level 2 fair value estimates have on large US and European banks' financial positions; (2) a 'case study' by pricing two common exotic derivatives and comparing the valuation results of two different assumptions of volatility (local vs. stochastic); and (3) a discussion of potential solutions to the problem surrounding FVA. Our findings are consistent with the argument that neutrality is supported by the exercise of prudence in achieving a faithful representation, since a non-conservative use of FVA can lead bank managers towards model misspecification error in the valuation of complex financial instruments. We conclude by arguing that the problem surrounding FVA can be mitigated if prudence is reinstated by standards setters.